Implementation of an ePortfolio to promote professional pathways: A case study of international students in Australian higher education - Hsieh, Yi-Jung Teresa (Journal of University Teaching and Learning Practice, 2025)
Given the current status of ‘English as a global language’, master’s and postgraduate programs in Applied Linguistics and TESOL are becoming an increasingly popular choice for international students in Australia and elsewhere. However, international students enrolled in such programs often lack practical experience and a potential employment pathway. In this respect, an ePortfolio as an assessment tool has been found to assist students to become independent thinkers as they develop self-regulated, purpose-driven behaviours during construction of their ePortfolio. However, building an ePortfolio is a new concept for many of the international students in Australian higher education. The aim of this case study research was thus to identify the support international students require in completion of their ePortfolios. Research data in this mixed method study was collected through two survey questionnaires applied to international students within a course requiring an ePortfolio as a major assessment item. Results indicate the need for more focused training for these students not only in how to structure their ePortfolios, but also more broadly in the employability skills needed in the Australian workplace. This research will help to improve the design of similar courses, and consequently to improve the learning experience for future international students undertaking such courses.